Preparation of nanoporous tungsten by liquid metal dealloying - Khuchitbaatar, Gerelmaa; Mangal, Delgermaa; Kato, Hidemi (Journal of Applied Science and Engineering A, 2021)
Liquid metal dealloying is the novel technique for generating porous structure from less noble metals. In this study, nanoporous tungsten was prepared by dealloying in a metallic melt from a tungsten-nickel precursor with different atomic compositions. All W-Ni precursors were immersed in Mg melt, and the dealloying temperature and time to obtain fully porous tungsten was studied. The results identified by X-ray diffraction (XRD) with Cu-Kα radiation show that obtained porous powder is single W. Microstructures were observed by scanning electron microscopy (SEM) shows that obtained powder has fully nanoporous structure. The ligament size was calculated from the image and the average pore, pore volume and specific surface area were examined by the BET method. According to the author’s knowledge, nanoporous tungsten was successfully prepared by liquid metal dealloying for the first time.